The roles of intrinsic disorder in protein interaction networks - Uversky, Vladimir N. (Henry Stewart Talks, 2013)
Introducing the protein intrinsic disorder concept and intrinsically disordered proteins (IDPs), Structural peculiarities of IDPs, Sequence peculiarities of IDPs, Abundance of IDPs and their functions, Intrinsic disorder in protein interaction networks, Peculiarities of disorder-based binding and regulation, Why are IDPs commonly involved in protein interactions?